2017
DOI: 10.3389/fmicb.2017.00611
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Potato virus Y Infectious Clone Tagged with the Rosea1 Visual Marker (PVY-Ros1) Facilitates the Analysis of Viral Infectivity and Allows the Production of Large Amounts of Anthocyanins in Plants

Abstract: Potato virus Y (PVY) is a major threat to the cultivation of potato and other solanaceous plants. By inserting a cDNA coding for the Antirrhinum majus Rosea1 transcription factor into a PVY infectious clone, we created a biotechnological tool (PVY-Ros1) that allows infection by this relevant plant virus to be tracked by the naked eye with no need for complex instrumentation. Rosea1 is an MYB-type transcription factor whose expression activates the biosynthesis of anthocyanin pigments in a dose-specific and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…This should improve even further with the implementation of mathematical modelling to predict responses of immune signaling [28] and linked primary metabolism. In addition, the production of PVY infectious clones [114][115][116] and advances in genetically encoded sensors in plants [117] will enable spatiotemporal monitoring of interactions between host and viral proteins during viral infection. The advanced genome editing technologies will allow an easier functional analysis of generated hypotheses [118].…”
Section: Future Outlookmentioning
confidence: 99%
“…This should improve even further with the implementation of mathematical modelling to predict responses of immune signaling [28] and linked primary metabolism. In addition, the production of PVY infectious clones [114][115][116] and advances in genetically encoded sensors in plants [117] will enable spatiotemporal monitoring of interactions between host and viral proteins during viral infection. The advanced genome editing technologies will allow an easier functional analysis of generated hypotheses [118].…”
Section: Future Outlookmentioning
confidence: 99%
“…In the past few years, different types of metal oxides and inorganic nanobiocides, such as ZnO [12,13], TiO 2 [14], and Ag, received much interest as alternative solutions in plant disease management. In particular, antimicrobial agents based on Ag nanoparticles (NPs) were intensively researched because of their excellent antifungal activity [14][15][16][17]. In fact, different studies reported the use of Ag-based nanocomposites loaded on different carrier systems, like graphene oxide (GO) [18], silicon oxide nanospheres, and porous carbon [18].…”
Section: Introductionmentioning
confidence: 99%
“…Those NPs act as immunogens for the production of highly specific polyclonal antiserum and monoclonal antibody [ 81 ]. Likewise, a transcription factor, Rosea1 tagged infectious clone of PVY was developed, conferring benefits to molecular farming by rapidly produced larger amounts of anthocyanins in biofactory crops [ 94 ].…”
Section: Applications/impactsmentioning
confidence: 99%